2021
DOI: 10.1007/s11846-021-00491-8
|View full text |Cite
|
Sign up to set email alerts
|

Crowdlending: mapping the core literature and research frontiers

Abstract: Peer-to-peer (P2P) lending uses two-sided platforms to link borrowers with a crowd of lenders. Despite considerable diversity in crowdlending research, studies in this area typically focus on several common research topics, including information asymmetries, social capital, communication channels, and rating-based models. This young research field is still expanding. However, its importance has increased considerably since 2018. This rise in importance suggests that P2P lending may offer a promising new scient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 150 publications
(174 reference statements)
0
7
0
1
Order By: Relevance
“…Hence, this topic has sparked research interest in terms of exploring how financial products and services are produced, delivered, and consumed ( Allen et al, 2021 ). However, many factors can impact every investment decision ( Ribeiro-Navarrete et al, 2021a ; Mollick, 2014 ), so this study examines Covid-19 and capital markets from a new perspective. Therefore, we contribute to the existing literature with new knowledge that helps to answer the implications of Covid-19 on the global economy, since, as authors such as Nozawa & Qiu, (2021) state, it has not yet been fully revealed.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, this topic has sparked research interest in terms of exploring how financial products and services are produced, delivered, and consumed ( Allen et al, 2021 ). However, many factors can impact every investment decision ( Ribeiro-Navarrete et al, 2021a ; Mollick, 2014 ), so this study examines Covid-19 and capital markets from a new perspective. Therefore, we contribute to the existing literature with new knowledge that helps to answer the implications of Covid-19 on the global economy, since, as authors such as Nozawa & Qiu, (2021) state, it has not yet been fully revealed.…”
Section: Introductionmentioning
confidence: 99%
“…However, the weakness of the peer-to-peer lending system lies in the limited information related to the post-loan history of the borrower. This is because the reputation of the borrower is generally the main reference for investors who are able to increase their trust in providing funds for peer-to-peer lending investment projects ( Ribeiro-Navarrete et al., 2021 ). Thus, transparency of data regarding potential borrowers will be advantageous to support investment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Beside that, Investor satisfaction is also an important factor that needs to be considered by platform managers, such as the ease of access to information related to platform management, details of funding projects, the latest developments in the platform and mobile application facilities ( Ribeiro-Navarrete et al., 2021 ). Therefore, to increase competitiveness and attract investors and borrowers, peer-to-peer lending platforms are encouraged to increase the disclosure of information they share with users ( Ribeiro-Navarrete et al., 2021 ). Moreover, in peer-to-peer lending transactions, the disclosure of information can reduce information asymmetry to minimize the potential for failure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations